To find the solutions of the quadratic equation -4x^2 + 6x - 3 = 0, we can use the quadratic formula:
x = (-b ± √(b^2 - 4ac)) / 2a,
where a = -4, b = 6, and c = -3.
Let's plug these values into the formula and solve for x:
x = (-6 ± √(6^2 - 4(-4)(-3))) / (2(-4))
x = (-6 ± √(36 - 48)) / (-8)
x = (-6 ± √(-12)) / (-8)
Since the discriminant (b^2 - 4ac) is negative, there will be no real solutions. The quadratic equation -4x^2 + 6x - 3 = 0 does not factor and has no real solutions.
Try to factor. If you can't, use quadratic formula
What are the solutions of the quadratic equation? -4x^2+6x-3=0
show work
1 answer